Site directed mutagenesis on highly conserved amino acid residues of choline kinase gene from neisseria meningitidis - Xiang, Cheong Jing (2022)
Neisseria meningitidis causes high transmissible disease known as invasive meningococcal disease (IMD) that is fatal. The best way to treat IMD is by antibiotics treatment. However, N. meningitidis has developed resistance to currently available antibiotics. Therefore, it is essential to discover new antimicrobial agents to combat the antibiotic resistant N. meningitidis strains. Choline kinase in N. meningitidis (NmCK) encoded by licA gene is one of the enzymes involved in cell membrane synthesis and inhibition of this enzyme in other bacteria has shown promising antimicrobial effect. However, basic biochemical properties and inhibitors of NmCK are still unknown. The present study aims to identify and modify important amino acid residues for NmCK catalysis that could be targeted for inhibition by performing two-step PCR site directed mutagenesis. Two aspartates (D153 and D170) in the CK motif of NmCK have been identified as highly conserved and chosen for mutagenesis into alanine. Two step PCR site-directed mutagenesis has successfully produced the full length D153A NmCK gene sequence without any unwanted mutation. Two fragments of D170A mutation have also been produced for subsequent combination into full length NmCK. Molecular modeling of wild type and D153A mutant NmCK was also performed and the model structures showed that the mutation of single amino acid did not change the overall structure of this enzyme. However, it is hypothesized that the mutation could alter the choline binding pocket. In conclusion, the D153A NmCK gene can be used for expression of mutant protein to study the importance of this residue in catalysis and inhibitor binding. The model structures generated can be used for molecular docking studies with potential inhibitors.